Analysis of the Iran-Israel War Conflict on Economic Implications in Indonesia - Lituhayu, Berlylia Nur Alina Lituhayu; Nasywa Mukhbita Nayla; Kyung Park, Hyun (LPPM Universitas Harapan Bangsa, 2024)
The conflict between Iran and Israel has been one of the flashpoints in the Middle East. However, in recent years, the conflict between these two countries has transcended regional boundaries and triggered turmoil at the global level. This study aims to analyze the Iran-Israel war conflict and examine the implications for the economy in Indonesia. The approach used is normative juridical by utilizing the method through library studies. The results show that Indonesia, as a developing country with the implementation of an open economic system that relies on the imported power sector, has an indirect relationship to the war conflict between Iran and Israel. The conflict has significantly impacted the Indonesian economy, especially with rising energy prices, inflation in international trade, and a significant decline in foreign investment. This study also emphasizes the importance of Indonesia maintaining a free and active foreign policy, as well as prioritizing diplomacy and peaceful conflict resolution in dealing with the implications of the war between Iran and Israel.